Controlling in the management of financial and economic security of enterprises - Shmyhol, Nadiia; Durnin Vіacheslav; Oleksenko, Yevhen (Management and Entrepreneurship: Trends of Development, 2018)
The relevance of the research topic is due to the need to justify the advantages of using controlling in the management of financial and economic security of enterprises in Ukraine. The purpose of the article is to develop theoretical positions and methodological recommendations for improving the controlling system in the management of financial and economic security of enterprises. The methodological basis of the research is comprehension of the totality of theories and scientific approaches to controlling, grounded in the works of national and foreign scientists. During the study, the following methods and approaches were used: methods of analysis and synthesis, abstract and concrete, historical method, factor analysis, structural and functional analysis, system approach. Findings. It is proved that the complex structure of the enterprise controlling system must meet all needs, correspond to the goals and objectives of a particular enterprise and be adapted to its internal and external environment. At the same time, it should be unique and flexible, allowing for any changes that depend on the needs and capabilities of the organization. It is also proved that in the complex index of financial firmness the following indicators were removed: coefficient of maneuverability of current assets, coefficient of assets mobility, index of fixed assets. In our opinion, these indicators are not so important to reflect the financial sustainability of the enterprise, since coefficient of maneuverability of current assets is directly related to the cash turnover ratio, and the coefficient of asset mobility is related to the current asset turnover.